Accounting for China's growth - Loren Brandt; Xiaodong Zhu (Institute for the Study of Labor (IZA), 2010)
China has achieved impressive growth over the last three decades. However, there has been debate over the sources of the growth, and the role of the intensive versus extensive margin. Growth accounting exercises at the aggregate level (Rawski and Perkins, 2008; Bosworth and Collins, 2008) suggest an equal role for both. For the non-agricultural sector, there have been doubts about the contribution of TFP improvements to growth. For the period between 1978 and 1998, Young (2003) stresses the role of labor deepening, including the reallocation from agriculture, while more recent analysis points to the role of rising rates of investment. Because labor reallocation across sectors, TFP growth at the sector level and investment are all inter-related, simple growth decompositions that are often used in the literature are not appropriate for quantifying their contributions to growth. In this paper, we develop a three-sector dynamic model to quantify the sources of China's growth. The sectors include agriculture, and within non-agriculture, the state and non-state components. We find only a modest role for labor reallocation from agriculture and capital deepening, and identify rising TFP in the non-state non-agricultural sector as the key driver of growth. We also find significant misallocation of capital: The less efficient state sector continues to absorb more than half of all fixed investment. If capital had been allocated efficiently, China could have achieved the same growth performance without any increase in the rate of aggregate investment. This has important implications for China as it tries to re-balance its growth. Finally, in light of important concerns over data, we examine the robustness of our key results to alternative data sets.
Keywords: E2; O4; 330; China; investment; growth; productivity; capital market distortions; Wirtschaftswachstum; Produktivität; Privatwirtschaft; Investition; Arbeitsmobilität; Allokation; Finanzmarkt; Unvollkommener Markt; Allokationseffizienz; Mehr-Sektoren-Modell; Dynamisches Modell; Schätzung; China